Revisiting the Fosse Temple at Tel Lachish - Ḳokh, ʿIdo (Journal of ancient Near Eastern religions, 2017)
This paper reconsiders the Late Bronze Age history of the Fosse Temple at Lachish and reconstructs its context vis-à-vis the broader role of the local Canaanite cult. During the reign of Amenhotep iii the structure’s plan was modified to conform to Egyptian-style and there was a profusion of Egyptian imports to the site, primarily associated with the cult of Hathor. These facts reflect the cultic innovations that were taking place in Egypt itself—the self-deification of Amenhotep iii and his consort, Tiye, including her depiction and worship as Hathor. It is consequently argued that the translation of Hathor/Tiye into the local goddess, Elat, and its continuous practice until the late 13th century bc echo the integration of Egypt within the indigenous cultural world.